Regional Renewable Energy Tariffs in Russia - Boute, Anatole (International Finance Corporation, Washington, DC, 2017)
The implementation of a functioning scheme for the support of electricity production from renewable energy sources (RES-E) in Russia has suffered from considerable delays. This report aims to analyze the role of regions as alternative drivers of RE policy in Russia. In particular, it examines how regions can stimulate the development of renewable energy sources in their electricity systems by establishing RES-E tariffs. The analysis focuses on the possibility for regional authorities to require network companies to purchase RES-E at regulated prices to compensate losses on their network. The implementation of regional renewable energy support policies in response to limited regulatory progress at federal government level is not uncommon in federal states. The analysis focuses on the possibility for regional authorities to require network companies to purchase RES-E at regulated prices to compensate losses on their network. The report is structured as follows: section one gives introduction. Section two introduces the division of powers for renewable energy regulation between the federal and regional levels of government. Section three reviews progress achieved so far with the regulation of RE support at federal government level. Section four discusses the policy objectives that, in the context of limited federal interest for RES-E, can drive regional clean energy policies. Section five analyzes federal regulatory and political obstacles to the adoption of regional RES-E tariffs in Russia, in particular RES-E tariffs for the electricity that network companies purchase to compensate losses on their network. Section six makes recommendations of ways to overcome the obstacles by making use of the broader regulatory powers under the Federal Energy Efficiency Law. For more publications on IFC Sustainability please visit www.ifc.org/sustainabilitypublications.